ANALISIS EKONOMI ALIH FUNGSI LAHAN PERTANIAN DI KOTA BEKASI (KASUS KECAMATAN BEKASI UTARA DAN BANTAR GEBANG) - Kamilah, Ahya (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2013)
The purpose of this study was to determine the factors that affect land use, assessing the economic value of land before and after conversion and analyze the impact of conversion on the income of farmers. The method used in this research is a case study (case study), to answer the research objectives include analysis used multiple regression analysis, land rent, the income of farmers and test T-test. The results showed that there are five factors that significantly affect land use, namely, age of farmers, the land held prior to conversion, net income before the conversion, the productivity of the land and farming experience, whereas no significant effect is the level of education and the number of dependents. Land rent value generated shows that the use of agricultural land has a land rent value is much smaller than the residential and industrial land. There is a significant decline in revenue between before and after conversion to the t value of 3857 and a decrease of 46 percent.